Library 3.0 : intelligent libraries and apomediation - Kwanya, Tom; Stilwell, Christine; Underwood, Peter G. (Chandos information professional series, 2015)
The emerging generation of research and academic library users expect the delivery of user-centered information services. 'Apomediation' refers to the supporting role librarians can give users by stepping in when users need help. 'Library 3.0' explores the ongoing debates on the 'point oh' phenomenon and its impact on service delivery in libraries. This title analyses Library 3.0 and its potential in creating intelligent libraries capable of meeting contemporary needs, and the growing role of librarians as apomediators